Implementation of the KIP Kuliah Program for Aspiration Path for Students of Universitas Mandiri Bina Prestasi - Octafiani Br. Sinulingga, Lidya; Siti Salmaniah Siregar, Nina; Masitho Batubara, Beby (Journal of Comprehensive Science, 2025)
The Indonesia Smart Card (KIP) Kuliah program is a government policy aimed at expanding access to higher education for students from underprivileged families. This study aims to analyze the implementation of the KIP Kuliah aspiration pathway program at Bina Prestasi Independent University, focusing on the selection process, aid distribution, and its impact on recipient students. A descriptive qualitative approach was used, with data collection through in-depth interviews, observation, and documentation. Research respondents included KIP Kuliah recipient students, supervisors, and university administrative staff. The results showed that the KIP Kuliah program has helped students from low-income families continue their higher education. The selection process is carried out transparently, but there are still technical obstacles, such as students' lack of understanding of administrative procedures and delays in fund disbursement. Additionally, students receiving the program stated that the assistance had a significant impact on reducing the economic burden on families, increasing motivation to learn, and encouraging academic achievement. This study recommends increased socialization of the program to new students, improvements in the fund disbursement mechanism, and enhanced coordination between the government, universities, and related parties. With these steps, the KIP Kuliah program is expected to operate more effectively and sustainably in supporting equitable access to higher education.